Studying Social Movements: Challenges and Opportunities for Participant Observation. Issue 11 (November 2013) - Uldam, Julie; McCurdy, Patrick
Abstract The research method of participant observation has long been used by scholars interested in the motivations, dynamics, tactics and strategies of social movements from a movement perspective. Despite participant observation being a common research method, there have been very few efforts to bring together this literature, which has often been spread across disciplines. This makes it difficult to identify the various challenges (and their interrelation) facing participant observers. Consequently, this article first reviews how participant observation roles have been conceptualised in general and then draws specific links to how the method has been used in the study of activism and social movements. In doing so, this article brings together key academic debates on participant observation, which have been considered separately, such as insider/outsider and overt/covert, but not previously been brought together.